Immunoregulatory role of platelet derivatives in the macrophage-mediated immune response - Anitua, Eduardo; Troya, María; Alkhraisat, Mohammad H. (Frontiers in Immunology, 2024)
Macrophages are innate immune cells that display remarkable phenotypic heterogeneity and functional plasticity. Due to their involvement in the pathogenesis of several human conditions, macrophages are considered to be an attractive therapeutic target. In line with this, platelet derivatives have been successfully applied in many medical fields and as active participants in innate immunity, cooperation between platelets and macrophages is essential. In this context, the aim of this review is to compile the current evidence regarding the effects of platelet derivatives on the phenotype and functions of macrophages to identify the advantages and shortcomings for feasible future clinical applications. A total of 669 articles were identified during the systematic literature search performed in PubMed and Web of Science databases. Of these, 27 articles met the inclusion criteria. Based on published findings, platelet derivatives may play an important role in inducing a dynamic M1/M2 balance and promoting a timely M1-M2 shift. However, the differences in procedures regarding platelet derivatives and macrophages polarization and the occasional lack of information, makes reproducibility and comparison of results extremely challenging. Furthermore, understanding the differences between human macrophages and those derived from animal models, and taking into account the peculiarities of tissue resident macrophages and their ontogeny seem essential for the design of new therapeutic strategies. Nevertheless, research on the combination of macrophages and platelet derivatives provides relevant information on the function and mechanisms of the immune response.